2016
DOI: 10.1021/acs.macromol.6b01712
|View full text |Cite
|
Sign up to set email alerts
|

Multicore Unimolecular Structure Formation in Single Dendritic–Linear Copolymers under Selective Solvent Conditions

Abstract: The conformational and thermodynamic properties of single dendritic–linear copolymers are investigated by analytical models and computer simulations. Applying poor solvent conditions on the dendritic part, these molecules are known to form single unimolecular micelle-like structures. A mean-field model applying the Daoud–Cotton approach and a surface tension argument is presented and suggests the splitting of the unimolecular single-core structure into a multicore structure with increasing dendrimers generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 56 publications
(98 reference statements)
2
33
0
Order By: Relevance
“…On the theory side, Wang et al [ 34 ], via a self-consistent field theory approach, have studied multicore micelle formation from linear ABC tri-block ter-polymers containing a solvophilic midblock and two mutually incompatible solvophobic head groups. In another study, Wengenmayr et al [ 51 ], via a mean-field model, observed the splitting of unimolecular single-core micelles of dendritic-linear copolymers to a multicore structure, with increasing dendrimer generation and decreasing solvent selectivity. On the computational side, DPD simulations which employ particle-based, mesoscale level modeling of the polymer chains and their assembly and dynamics, have turned out to be an adaptable and reasonably successful tool for examining the formation and assembly responses of polymeric micelles [ 46 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the theory side, Wang et al [ 34 ], via a self-consistent field theory approach, have studied multicore micelle formation from linear ABC tri-block ter-polymers containing a solvophilic midblock and two mutually incompatible solvophobic head groups. In another study, Wengenmayr et al [ 51 ], via a mean-field model, observed the splitting of unimolecular single-core micelles of dendritic-linear copolymers to a multicore structure, with increasing dendrimer generation and decreasing solvent selectivity. On the computational side, DPD simulations which employ particle-based, mesoscale level modeling of the polymer chains and their assembly and dynamics, have turned out to be an adaptable and reasonably successful tool for examining the formation and assembly responses of polymeric micelles [ 46 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another case of pseudocavity was studied in copolymer dendrimers [ 95 ] by Monte‐Carlo simulations. It was shown that the formation of a hollow core for higher ( G > 6) generations in copolymer dendrimers is possible due to poor quality of solvent for inner segments and the segregation effect between terminal and inner segments (see green curves in Figure b,c).…”
Section: Perspectives: Copolymer Dendrimersmentioning
confidence: 99%
“…Reproduced with permission. [ 95 ] Copyright 2016, American Chemical Society. “Pseudocavity” case, since the minimum density in the inner volume of copolymer dendrimer for selective solvent (green in part d)) is equal or higher than the density of copolymer dendrimer for nonselective solvent (green in part b), i.e., 0.1 ≥ 0.2/S 4/5 .…”
Section: Perspectives: Copolymer Dendrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of being a non-specific model of polymer dynamics, the BFM was successfully used to study a large variety of physical effects in two- and three dimensions like, e.g., static [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and dynamic [ 18 , 30 , 31 , 32 , 33 ] properties of linear chains, polymer rings [ 27 , 34 ], polymer blends and interfaces [ 35 , 36 ], gels and networks [ 37 ], glass transition [ 38 , 39 , 40 ], polymer blends [ 41 ], (co)polymers at surfaces [ 42 ], polymer brushes in good solvents [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ], polymer thin films [ 50 , 51 , 52 ], equilibrium polymers [ 29 , 53 , 54 ], general self-assembly [ 55 , 56 , 57 ], networks and gel point [ 58 , 59 , 60 , 61 ], olympic gels [ …”
Section: Introductionmentioning
confidence: 99%